Challenges and Opportunities of Outdoor Play Activities on Early Childhood Motor Competence: A Bibliometric Analysis - Heru Andika; Gusril Gusril; Anton Komaini; Yanuar Kiram; Syahrial Bakhtiar; Bafirman Bafirman; Padli Padli; Sri Gusti Handayani (Jurnal Sporta Saintika, 2025)
Research on outdoor play activities (OPA) and early childhood motor skills has received considerable attention due to its significant role in supporting children's physical, cognitive, and social development. However, the global literature has not been comprehensively mapped over a long period. This study aims to analyze the trends, structure, and dynamics of OPA research during the period 2006–2026. The study uses a bibliometric approach. Data were obtained from the Scopus database, consisting of 211 systematically selected publications, and then analyzed using VOSviewer software through visualization of collaboration networks, co-citations, and keyword co-occurrences. The study findings indicate that the highest number of publications in 2021 was 25, with a significant increasing trend since 2018. Dominant keywords include children, motor skills, physical activity, and outdoor play, reflecting the multidisciplinary nature of health, education, and the environment. Influential authors and publications have largely focused on the importance of social and environmental factors on children's physical activity (Brown et al., 2009, Xue et al., 2007, and Boldemann et al., 2006). Research collaboration is strongest in developed countries such as the United States, Australia, and Canada, while contributions from developing countries remain limited. This study demonstrates that OPA has evolved into a multidisciplinary field that supports holistic child development. In practice, stronger global collaboration can be achieved through international research partnerships and shared data platforms, while local exploration should involve culturally relevant play programs and community-based interventions, particularly in developing countries, to generate context-specific evidence and inform education and health policy.